WORK AND LIFE SATISFACTION THROUGH EMIL IN PARIS TV SERIES - TANER GEZDİGELDİ , Ceren; KARAAZİZ, Meryem (SSD Journal, 2023)
Work and life satisfaction is a topic that psychology and business psychology focus on. The concept of work and life satisfaction first began to be considered in the 1920s. Basically, work and life satisfaction are two concepts that affect each other. Life satisfaction is in the hands of a person and their desires the closer these two are to each other, the higher the life satisfaction. We can't say that job satisfaction is direct life satisfaction, but job satisfaction seems to affect life satisfaction very much. In this study, document review, which is one of the qualitative research methods, was used. Emily In Paris is an American television series in the comedy and drama genre. Series 2.October.It premiered on Netflix in 2020. The series consists of 1 season 10 episodes. Events begin when Emily, the lead actress of the series, goes to Paris for work. The idea of going to Paris excites Emilly very much. He goes to Paris with great excitement. The cultural conflict he experienced when he went to Paris, his loneliness and his inability to accept Emily in his work life affect his work and life satisfaction. Emily does not give up in the face of this situation, jumping from every obstacle in front of her continues her path. First, he found himself a friend, so his life satisfaction increases, and then as the projects he offers in the company are approved, as he signs successful jobs, his job satisfaction also increases. Work and life satisfaction are two concepts that affect each other. According to the end of the series, Emily's work and life satisfaction increases and she is very happy. The aim of this study is to explain the concept of work and life satisfaction, two concepts that affect one another, by analyzing the Emily in Paris series. The series also features different psychological processes that stand out. The most prominent concept of work and life satisfaction is discussed in detail in the study.